Gravitation-Based 3-D Redeployment Schemes for the Mobile Sensors and Sink in Gas Leakage Monitoring - He Li; Yang Yang; Xuesong Qiu; Zhipeng Gao; Guizhen Ma (IEEE Access, 2017)
Gas leakage is one of the most frequent types of accidents in the petrochemical industry. It is imperative to use mobile sensors to monitor such an accident area. The new and effective way is to use drones and helicopters that spray wireless sensors from the air to monitor harmful gases and to locate the gas leaking source. However, the sprayed wireless sensors will be distributed randomly around the accident area, and it is a challenge to obtain effective coverage. This paper proposes a gravitation-based redeployment algorithm for sensors (GRSS) that considers the virtual boundary forces and the gas concentration in a 3-D accident monitoring area. A priority-based redeployment algorithm for sensors (PRSS) is proposed to further improve the coverage and simplify the 3-D redeployment problem. PRSS considers the layer priorities of the monitoring area to control the movements of the mobile sensors. The simulation results show that the GRSS and PRSS methods can achieve better coverage and utilize less distance compared with the random algorithm and 3-D self-deployment.